Demande de sécurité des véhicules et normes automobiles depuis les années 1960 - Marine Moguen-Toursel (L'Atelier du CRH)
This paper focuses on the emergence of road safety at the Community level as an important societal stake, answering the very urgent problem of number of deaths on the roads (which was particularly high at the beginning of the 1970s). This awareness is related to the introduction of public institutions on these issues at the national level as well as at the Community one.Nevertheless, transformations in terms of regulations are quite slow to appear. The European Commission has to invent new procedures for obtaining improvements on these fields.Since high profits have been evaluated in terms of penetration of vehicle safety innovations on European automobile markets (which implies a rise of competition for this industry), pressure in favour of a uniform regulation (in particular between Community and International standards) are stronger and R&D investments bigger (even if they remain much lower than in the United States). The main obstacle today is the lack of interest of European consumers for these technologies and the misuse of these safety tools on board of their vehicles.In terms of governance, these issues are now considered by a growing number of economic actors (it is interesting to show that first economic actors on these fields were car makers, then public institutions and lastly consumers associations). Working groups are evolving toward an integrated approach making various economic actors intervene in discussion forums much above the final decision is taken.